2007
DOI: 10.1080/17482960701549681
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteomic profiling of cerebrospinal fluid between living and post mortem ALS and control subjects

Abstract: Neurodegenerative diseases, including amyotrophic lateral sclerosis (ALS), lack definitive diagnostic tests or biomarkers of disease progression. Most studies that investigate protein abnormalities in ALS have used biofluids such as blood or cerebrospinal fluid (CSF), while some have used post mortem tissue or CSF samples. Since ALS disease progression and post mortem effects probably induce significant alterations to protein modifications or proteolysis, we directly examined the CSF proteome from ALS subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 19 publications
(28 reference statements)
2
19
0
Order By: Relevance
“…The biomarker panel distinguished ALS cases from neurologic disease controls, consistent with previous proteomic studies. 3,8 Our data expand the previous studies and show promise that a biomarker panel could be developed for aiding in the diagnosis of ALS. Future validation studies should incorporate samples from multiple clinics and from patients with syndromes that mimic ALS.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The biomarker panel distinguished ALS cases from neurologic disease controls, consistent with previous proteomic studies. 3,8 Our data expand the previous studies and show promise that a biomarker panel could be developed for aiding in the diagnosis of ALS. Future validation studies should incorporate samples from multiple clinics and from patients with syndromes that mimic ALS.…”
Section: Discussionsupporting
confidence: 80%
“…[2][3][4][5][6][7][8] While many of these studies have provided clues about pathogenetic mechanisms involved in the disease, most have examined only a small number of proteins. Several studies have examined proteomic profiles of patients with ALS compared to various control groups.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…During the last few years, transcriptomics and proteomics studies have attempted to identify, from a global perspective, specific subsets of genes and proteins that might be used as surrogate markers of disease [9][10][11][12] . Although further validation is needed, these studies highlight that it is likely more appropriate to isolate a panel of markers, rather than a single gene or protein, in order to determine disease severity.…”
Section: Introductionmentioning
confidence: 99%
“…Another protein potentially useful as a biomarker is cystatin C, a 13.4 kDa protein exhibiting increased CSF levels in ALS patients over controls. This has been proposed in one comparative study that also found reduced transthyretin peaks in ALS patients over non-ALS controls (Ranganathan et al, 2007). CSF analysis seems a good approach for the discovery of important biomarkers for ALS, as it exhibits a reduced abundance of proteins that need to be excluded from the samples before proteomic analysis over serum/ plasma.…”
Section: Cerebrospinal Fluidmentioning
confidence: 98%